National Interests are above International Affairs: Indonesian-Israeli Intelligence Operations on the Purchase of A-4 Skyhawks, 1978-1982 - Hadiyanto, Fidel Satrio; Sulistiyono, Singgih Tri (Journal of Maritime Studies and National Integration, 2024)
This study examines Operation Alpha, an intelligence operation conducted by Indonesia and Israel to facilitate the purchase and delivery of 32 Douglas A-4 Skyhawk aircraft from Israel to Indonesia between 1978 and 1982. Despite Indonesia's official policy of non-recognition towards Israel due to its support for Palestinian independence, the Indonesian government under President Soeharto pursued a pragmatic approach to address the urgent need for modernizing its aging military equipment. Through a series of negotiations involving the United States, Indonesia reached an agreement with Israel to procure the aircraft at a lower cost and with faster delivery compared to purchasing directly from the US. The successful completion of Operation Alpha not only bolstered Indonesia's defense capabilities but also marked the beginning of discreet military and economic cooperation between the two countries that continued until the reform era, despite the absence of official diplomatic relations. This study highlights the prioritization of national interests over international affairs in Indonesia's foreign policy during the Soeharto era and the role of intelligence agencies in facilitating clandestine cooperation between states with conflicting official stances.